A COMPREHENSIVE BIM IMPLEMENTATION MODEL FOR DEVELOPING COUNTRIES - Oluseye Olugboyega; Abimbola Windapo (Journal of Construction Project Management and Innovation)
BIM implementation in the construction industry can be used to build the quality and competitiveness of AEC practices in the construction industry. However, to ensure significant and sustained BIM implementation in developing countries, it becomes important to investigate the appropriate strategies for significant and sustained BIM implementation in developing countries. Therefore, this study investigated the strengths and shortcomings of the BIM implementation strategies in use in the developed countries so as to identify a comprehensive set of BIM implementation strategies that will bring about a significant and sustained BIM implementation in the developing countries. The study developed a comprehensive BIM implementation model based on a theoretical background that was built from a meta-synthesis of studies on BIM adoption and theoretical perspectives from Implementation Process Theory. The model features top management commitment strategies, motivation strategies, capacity development strategies, and application strategies as the constructs for achieving a successful and sustained BIM implementation. The findings of the study are useful for stimulating the growth and technological development of construction industries in developing countries.